Vanadyl iodate second-order nonlinear optical crystal material, preparation and application thereof

By preparing the second-order nonlinear optical crystal VO2(H2O)(IO3) of vanadate, the problem of the difficulty in synthesizing NCS structure from inorganic crystal materials has been solved, achieving efficient laser frequency conversion and photoelectric modulation effects, and has broad application prospects.

CN120041931BActive Publication Date: 2025-12-05OCEAN UNIV OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510038307.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-12-18
Filing Date
2025-01-10
Publication Date
2025-12-05
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

Existing inorganic crystal materials are difficult to synthesize in a custom manner with second-order nonlinear optical crystals having non-centrosymmetric structures, which limits their laser frequency conversion capabilities.

Method used

A second-order nonlinear optical crystal material VO2(H2O)(IO3) of vanadate is provided. It is prepared by hydrothermal synthesis at 150-230℃ to form a Pca21 space group structure with orthorhombic crystal system, which is combined with zigzag chains and hydrogen bonds to form a 3D framework structure.

Benefits of technology

This crystal material exhibits a frequency doubling effect approximately 18.0 times that of KDP under 1200nm laser light and approximately 1.5 times that of KTP under 2100nm laser light. It also has a thermal stability temperature of 240℃, making it suitable for applications such as laser frequency conversion, optoelectronic modulation, and holographic storage of laser signals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120041931B_ABST
    Figure CN120041931B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of vanadium iodate second-order nonlinear optical crystal material and its preparation and application, the chemical formula is VO2 (H2O) (IO3), molecular weight is 275.86, belongs to orthorhombic system, its space group is Pca21, cell parameter is α=β=γ=90 °, Z=4, cell volume is The vanadium iodate crystal material of the present application has excellent second-order nonlinear optical performance, under 1200nm laser irradiation, powder frequency doubling intensity is about 18.0 times of potassium dihydrogen phosphate crystal (KDP), under 2100nm laser irradiation, powder frequency doubling intensity is about 1.5 times of potassium titanyl phosphate (KTP), and phase matching can be realized.In addition, vanadium iodate crystal material also has large birefringence, reaches 0.184 at 546nm.The above research results show that the crystal has wide application prospect in the field of laser frequency conversion, photoelectric modulation, laser signal holographic storage etc..
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of optical crystal materials, and relates to a vanadyl-iodate second-order nonlinear optical crystal material and preparation and application thereof. BACKGROUND

[0002] Nonlinear optical crystal materials with second harmonic generation (SHG) properties play a vital role in modern laser science and technology, which can be attributed to their laser frequency conversion capability that can be applied to extend the output spectral range of laser light sources. A prerequisite for a second-order nonlinear optical (NLO) crystal material is to have a crystallographically noncentrosymmetric (NCS) structure, and the presence of asymmetric structural units in the molecular structure can promote the formation of a macroscopic NCS structure. Currently commercialized nonlinear optical materials include beta-barium borate (BBO), lithium borate (LBO), potassium dihydrogen phosphate (KDP), and potassium titanyl phosphate (KTP). In the past two decades, although great efforts and explorations have been made to establish the correlation between the crystal structure and the SHG property, it is still very difficult to customize and synthesize a crystal with a NCS structure due to the fact that the unfavorable dipole-dipole interaction and / or steric effect in inorganic crystal materials favor the formation of a centrosymmetric (CS) structure rather than a NCS structure. Therefore, developing a new NCS material with strong SHG response is a major challenge in the field of inorganic optical functional materials. SUMMARY

[0003] The purpose of the present application is to provide a vanadyl-iodate second-order nonlinear optical crystal material and preparation and application thereof. The crystal exhibits a huge SHG response, and the powder frequency doubling intensity thereof is about 18.0 times that of the benchmark frequency doubling crystal potassium dihydrogen phosphate (KDP) under 1200 nm laser irradiation, and is about 1.5 times that of the infrared benchmark frequency doubling crystal potassium titanyl phosphate (KTP) under 2100 nm laser irradiation. The crystal can achieve phase matching, and shows that the crystal is a second-order nonlinear optical crystal material with important potential application value.

[0004] The purpose of the present application can be achieved by the following technical solutions.

[0005] One of the technical solutions of the present application is to provide a vanadyl-iodate second-order nonlinear optical crystal material, which has a chemical formula of VO2(H2O)(IO3) and a molecular weight of 275.86.

[0006] Further, the crystal material belongs to an orthorhombic system, has a space group of Pca21, and has a unit cell parameter of a=10. 1 α=β=γ=90°, Z=4, and a unit cell volume of V= 1

[0007] Further, the unit cell parameter of the crystal material is α = β = γ = 90°, Z = 4, the cell volume is 1 1 1 1 A3

[0008] The crystal structure of the vanadium oxyiodide compound of the present application can be described as follows: in the vanadium oxyiodide crystal, the six-coordinated V 5+ cation is connected with six oxygen atoms (one terminal oxygen atom, two bridging oxygen atoms, two oxygen atoms from iodate groups in different chelating modes, and one oxygen atom from a water molecule) to form a [V(1)O5(H2O)] 5- octahedron, in which the bond length of the vanadium-oxygen bond is Each [V(1)O5(H2O)] 5- octahedron is connected with the adjacent [V(1)O5(H2O)] 5- octahedron through the shared O(3) and O(5) atoms, forming a zigzag chain [VO2(H2O)(IO3)] ∞ along the c axis. 5+ The cation is coordinated with three O atoms to form a trigonal pyramid geometry (in which the O-I-O included angle is 96.26(14)-100.41(11)°, and the I-O bond length is [I(1)O3] - group is connected to the two sides of the zigzag chain in a bidentate bridging manner through the edge-shared oxygen atom O(1). Not only are there weak hydrogen bonds between the zigzag chain and the coordinated H2O molecule (O6-H6A … O2 and O6-H6A … O1), but there are also weak hydrogen bonds between the adjacent zigzag chains (O6-H6B … O1). This connection mode through intermolecular hydrogen bonds leads to the formation of a two-dimensional (2D) [VO2(H2O)(IO3)] ∞ layer in the ac plane. Interestingly, the layers are stacked in parallel, in an -AAAA- order along the c axis, and are connected through weak I(1) … O(2) intermolecular interactions, overall forming a pseudo-three-dimensional (3D) framework structure along the ab plane.

[0009] The second technical scheme of the present application provides a preparation method of a vanadate second-order nonlinear optical crystal material, characterized in that: first, a vanadium source, an iodine source, a sulfur source, and water are mixed to form initial mixed raw materials, wherein the sulfur source serves as a mineralizer and provides an acidic environment, thereby being more conducive to the growth of the crystal material; and then the initial mixed raw materials are placed in a sealed hydrothermal condition for reaction and crystallization, so as to obtain the target product.

[0010] Further, the vanadium source is vanadium pentoxide; the iodine source is iodic acid; and the sulfur source is sulfuric acid.

[0011] Further, the molar ratio of vanadium element, iodine element and sulfur element in the initial mixed raw material is 1:(0.5-30):(0.5-50).

[0012] Further, the molar ratio of vanadium element, iodine element and sulfur element in the initial mixed raw material is 1:(0.5-30):(0.5-50).

[0013] Further, the temperature of the crystallization hydrothermal reaction is 150-230 DEG C, and the crystallization time is not less than 24 h. Preferably, the temperature of the crystallization hydrothermal reaction is 180-230 DEG C, and the crystallization time is not less than 48 h. Meanwhile, after the crystallization is completed, the temperature is cooled to room temperature at a cooling rate of 0.5-15 DEG C / h, preferably at a cooling rate of 0.5-6 DEG C / h.

[0014] The third technical scheme of the present application provides a vanadate salt second-order nonlinear optical crystal material and an application thereof. The crystal material is used for visible and mid-infrared laser frequency doubling output. Preferably, the crystal material is used for visible and infrared laser beam frequency doubling harmonic output.

[0015] Further, the crystal material is used in frequency doubling generators, optical parametric oscillators, optical parametric amplifiers and photoelectric rectifiers.

[0016] The crystal material of the present application is used in laser frequency converters. The vanadium oxyiodide crystal material has a huge frequency doubling effect. The powder frequency doubling effect thereof is about 18.0 times that of the reference frequency doubling crystal KDP under 1200 nm laser irradiation, and the powder frequency doubling intensity thereof is about 1.5 times that of the infrared reference frequency doubling crystal KTP under 2100 nm laser irradiation, and the crystal material is I-type phase matching. In addition, the band gap of the crystal material is 2.81 eV, and the thermal stability temperature is 240 DEG C. Thus, the crystal material has a wide application prospect in the field of second-order nonlinear optics.

[0017] Compared with the prior art, the present application has the following advantages:

[0018] (1) The present application provides a new inorganic crystal material, vanadium oxyiodide compound, which has a huge frequency doubling effect. The powder frequency doubling effect thereof is about 18.0 times that of the KDP crystal under 1200 nm laser irradiation, and the powder frequency doubling intensity thereof is about 1.5 times that of the KTP under 2100 nm laser irradiation. The birefringence value thereof is 0.184 under 546 nm laser, and the crystal material can realize I-type phase matching. In addition, the optical band gap of the crystal material is 2.81 eV, and the thermal stability temperature reaches 240 DEG C. Thus, the crystal material has a wide application prospect in the fields of laser frequency conversion, photoelectric modulation, laser signal holographic storage and the like.

[0019] (2) The present application provides a preparation method of the vanadium oxyiodide crystal material, which is prepared by hydrothermal synthesis method with mild reaction condition, and high-purity crystalline sample can be obtained at a high yield through hydrothermal crystallization at a temperature of 150-230 DEG C, the method is simple and the condition is mild, which is beneficial to realize large-scale industrial production.

[0020] (3) The vanadium oxyiodide crystal material of the present application can be applied to a laser frequency converter, and can be used for doubling the frequency of visible and infrared laser beams. BRIEF DESCRIPTION OF DRAWINGS

[0021] Figure 1 is a schematic diagram of the crystal structure of vanadium oxyiodide;

[0022] Figure 2 is a comparison of X-ray diffraction patterns;

[0023] Figure 3 is the ultraviolet-visible-near infrared absorption spectrum of sample 1#;

[0024] Figure 4 is the infrared spectrum (2.5-25 μm) spectrum of sample 1#;

[0025] Figure 5 is the thermogravimetric analysis spectrum of sample 1#;

[0026] Figure 6 is the second harmonic signal diagram of sample 1# and KDP sample with a size in the range of 200-280 μm;

[0027] Figure 7 is the second harmonic phase matching diagram of sample 1# and KDP sample at a wavelength of 1200 nm;

[0028] Figure 8 is the second harmonic signal diagram of sample 1# and KTP sample with a size in the range of 200-280 μm;

[0029] Figure 9 is the second harmonic phase matching diagram of sample 1# and KTP sample at a wavelength of 2.1 μm;

[0030] Figure 10 is the birefringence test diagram of sample 1# at a wavelength of 546 nm. DETAILED DESCRIPTION

[0031] The present application will be described in detail below in combination with the drawings and specific embodiments. The present embodiment is implemented on the premise of the technical scheme of the present application, and detailed implementation and specific operation process are given, but the protection scope of the present application is not limited to the following examples.

[0032] In the following examples, unless otherwise specified, the raw materials or process technology are all conventional commercially available products or conventional processing technology in the art.

[0033] Example 1

[0034] Hydrothermal synthesis of samples

[0035] The vanadium source, iodine source, sulfur source (98wt% sulfuric acid) and water were mixed in a certain proportion to form the starting material, which was sealed in a hydrothermal reactor with a polytetrafluoroethylene liner, heated to the crystallization temperature, and then slowly cooled to room temperature at a certain rate after a certain period of time. The yellow transparent block-shaped vanadium oxyiodide crystals were obtained after filtration and washing.

[0036] The relationship between the type and ratio of raw materials in the initial mixture, the crystallization temperature, the crystallization time and the sample number is shown in Table 1.

[0037] Table 1 Correspondence of samples with raw materials and synthesis conditions

[0038]

[0039]

[0040] Example 2

[0041] Crystal structure analysis

[0042] Single crystal X-ray diffraction and powder X-ray diffraction methods were used to analyze the structure of samples 1#-6#.

[0043] The single crystal X-ray diffraction test was performed on a D8 VENTURE CMOS X X-ray single crystal diffractometer of Bruker Company in Germany. The crystal size was 0.12 x 0.07 x 0.06 mm 3 ; the data collection temperature was 293 K, the diffraction light source was graphite monochromated Mo-Ka ray, and the wavelength was The scanning mode was ω; the data was processed by absorption correction using the Multi-Scan method. The structure analysis was completed using the SHELXTL-97 program package; the positions of heavy atoms were determined by direct method, and the coordinates of the remaining atoms were obtained by difference Fourier synthesis method; all atomic coordinates and anisotropic thermal parameters were refined using full matrix least squares method based on F 2 .

[0044] The powder X-ray diffraction test was performed on an X-ray powder diffractometer of Bruker D8 type of Bruker Company in Germany, and the test conditions were fixed target monochromatic light source Cu-Ka, and the wavelength was The voltage and current are 40kV / 20A, the slits DivSlit / RecSlit / SctSlit are 2.00deg / 0.3mm / 2.00deg respectively, the scanning range is 5–70°, and the scanning step size is 0.02°.

[0045] The single-crystal X-ray diffraction results showed that samples 1# to 6# had the same chemical formula and crystal structure, with the chemical formula VO2(H2O)(IO3), a molecular weight of 275.86, belonging to the orthorhombic crystal system, with a space group of Pca21 and a unit cell parameter of [missing information]. α=β=γ=90°, Z=4, cell volume is

[0046] Taking sample 1# as a typical example, its crystal structure data is as follows: α=β=γ=90°, Z=4, cell volume is Its crystal structure is as follows Figure 1 As shown.

[0047] The powder X-ray diffraction test results showed that the peak positions of samples 1# to 6# were basically the same, while the peak intensities were slightly different.

[0048] Taking sample 1# as a typical example, such as Figure 2 As shown, the X-ray diffraction pattern obtained by grinding sample 1# into powder and then performing X-ray diffraction test is consistent with the X-ray diffraction pattern obtained by simulating the crystal structure based on its single-crystal X-ray diffraction. The peak positions and peak intensities are consistent, indicating that the obtained sample has high purity.

[0049] Example 3:

[0050] Ultraviolet transmission spectroscopy test

[0051] The ultraviolet transmission spectrum of sample 1# was measured using an Agilent Technologies Cary 5000 UV-Vis-NIR spectrophotometer. The results are as follows: Figure 3 As shown, the ultraviolet absorption cutoff edge of this compound is 442 nm, and the corresponding optical band gap is 2.81 eV.

[0052] Example 4:

[0053] Infrared spectroscopy test

[0054] The infrared spectroscopy of sample 1# was performed using a Nicolet iS10 Fourier transform infrared spectrometer from Thermo Fisher Scientific, Inc., USA. The results are as follows: Figure 4 As shown, 870cm -1 715cm -1 and 686cm -1The infrared absorption peak at 3496 cm⁻¹ is attributed to the stretching vibration peak of the IO bond, while the OH stretching vibration peak and the in-plane bending vibration peak are located at 3496 cm⁻¹. -1 3371cm -1 and 1597cm -1 At this location, these infrared characteristic peaks are consistent with the single-crystal structure.

[0055] Example 5:

[0056] Thermogravimetric test

[0057] Thermogravimetric analysis (TGA) of sample #1 was performed on a Netzsch STA 409PC thermogravimetric analyzer from Netzsch GmbH, Germany. The results are as follows: Figure 5 As shown, by Figure 5 It can be seen that the compound is stable up to 240℃, exhibiting good thermal stability.

[0058] Example 6:

[0059] Frequency doubling test experiment and results

[0060] The frequency doubling test experiment for sample #1 is as follows: A 1200nm wavelength laser generated by a tunable laser testing system (Amplitude, Horizon II) was used as the fundamental frequency light to irradiate the crystal powder under test. The generated second harmonic was detected using a photomultiplier tube, and the harmonic intensity was displayed on an oscilloscope. The crystal sample and the reference frequency doubling crystals KDP and KTP were ground separately, and crystals of different particle sizes were separated using a standard sieve. The particle size ranges were less than 26, 26–50, 50–74, 74–105, 105–150, 150–200, and 200–280 μm, respectively. The trend of the frequency doubling signal intensity with particle size was observed to determine whether phase matching could be achieved. Under the same test conditions, the second harmonic intensity generated by the sample and the reference frequency doubling crystals KDP and KTP was compared to obtain the relative magnitude of the sample's frequency doubling effect.

[0061] Test results show that the vanadium-iodide-oxygen compound crystal exhibits a significant frequency doubling effect. Under 1200 nm wavelength laser irradiation, the frequency doubling signal intensity is 18.0 times that of the reference frequency doubling crystal KDP (e.g., Figure 6 ), which can achieve type I phase matching (such as Figure 7 Under 2100nm wavelength laser irradiation, the frequency doubling signal intensity is 1.5 times that of the reference infrared frequency doubling crystal KTP (e.g., Figure 8 Similarly, type I phase matching can also be achieved (e.g. Figure 9 ).

[0062] Example 7:

[0063] Birefringence test experiment and results

[0064] The birefringence of the crystal VO2(H2O)(IO3) was tested by a polarizing microscope (ZEISS Axio Scope.A1) equipped with a Berek compensator. The wavelength of the light source was 546 nm. The birefringence was calculated according to the following formula:

[0065] AR = |Ne-No| x T = An x T

[0066] Wherein, AR represents the optical path difference, An represents the birefringence, and T is the thickness of the crystal. The positive and negative rotation of the compensation will produce a relative retardation. The boundaries between the first-order, second-order and third-order interference colors are clear, so the relative error is small. In order to improve the accuracy of the birefringence, we selected transparent flaky VO2(H2O)(IO3) crystals for measurement.

[0067] The test results show that the compound vanadium iodine oxygen crystal exhibits strong optical anisotropy, reaching 0.184 at 546 nm (as shown in FIG. 2), which is better than the birefringence efficiency of most commonly used commercial birefringent crystals. Figure 10

[0068] The above description of the embodiments is for the purpose of facilitating the understanding and use of the invention by those skilled in the art. Those skilled in the art can obviously make various modifications to these embodiments, and apply the general principles described herein to other embodiments without having to go through creative labor. Therefore, the present application is not limited to the above embodiments, and the improvements and modifications made by those skilled in the art within the scope of the present application without departing from the scope of the present application should be within the protection scope of the present application.​

Claims

1. A vanadyl-iodate second-order nonlinear optical crystalline material, characterized in that, The chemical formula is VO2(H2O)(IO3), the molecular weight is 275.86, and it belongs to the orthorhombic system, and the space group is Pca 21, the cell parameters are a = 13.85~14.05 Å, b =6.87~7.07 Å, c = 4.75~4.95 Å, α = β = gamma = 90°, Z = 4, the cell volume is V = 451.1~491.1Å 3 .

2. The vanadyl iodate second-order nonlinear optical crystal material of claim 1, characterized in that, The cell parameters of the crystal material are a = 13.9520 Å, b = 6.9686 Å, c = 4.8452 Å, α = 90°, β = 90°, gamma = 90°, Z = 4, and the cell volume is V = 471.08 Å 3 .

3. The method of producing a vanadyl iodate salt second-order nonlinear optical crystal material according to claim 1 or 2, characterized by, The initial mixed raw material is formed by mixing vanadium source, iodine source, sulfur source and water, and then is reacted and crystallized under a sealed hydrothermal condition to obtain the target product.

4. The method of claim 3, wherein the vanadyl iodate second-order nonlinear optical crystal material is prepared by the following steps: The vanadium source is vanadium pentoxide; the iodine source is iodic acid; and the sulfur source is sulfuric acid. ​ 5. The method of claim 3, wherein the vanadyl iodate second-order nonlinear optical crystal material is prepared by the following steps of: In the initial mixed raw material, the molar ratio of vanadium element, iodine element and sulfur element is 1:(0.5-30):(0.5-50). ​ 6. The method of claim 3, wherein the vanadyl iodate second-order nonlinear optical crystal material is prepared by the following steps of: In the initial mixed raw material, the molar ratio of vanadium element, iodine element and sulfur element is 1:(1-20):(1-20). ​ 7. The method for preparing a vanadate second-order nonlinear optical crystal material according to claim 3, characterized in that, The crystallization temperature is 150-230 DEG C, and the crystallization time is not less than 24 h.

8. The use of the vanadyl-iodate salt second-order nonlinear optical crystal material according to claim 1 or 2, characterized in that, The crystal material is used for visible-mid-infrared laser frequency doubling output.

9. The use of a vanadyl iodate second-order nonlinear optical crystal material according to claim 8, characterized in that, The crystal material is used in a frequency doubling generator, an optical parametric oscillator, an optical parametric amplifier and an optical rectifier.

Citation Information

Patent Citations

  • Method for growing large-size vanadium sodium iodate crystal by using hydrothermal method

    CN102400222A

  • Non-linear optical crystal iodic acid vanadium potassium

    CN102534786A